The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1203/pdr.0b013e31818912d2
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Injury in Term Newborns With Neonatal Encephalopathy

Abstract: White matter injury (WMI) is the characteristic pattern of brain injury detected on magnetic resonance imaging in the premature newborn. Focal noncystic WMI is increasingly recognized in populations of term newborns. The aim of this study was to describe the occurrence of focal noncystic WMI in a cohort of 48 term newborns with encephalopathy studied with magnetic resonance imaging at 72 Ϯ 12 h of life, and to identify clinical risk factors for this pattern of injury. Eleven newborns (23%; 95% CI 11-35) were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
70
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(79 citation statements)
references
References 37 publications
5
70
0
4
Order By: Relevance
“…Perinatal WMI (including periventricular leukomalacia) was the most common finding, which was seen in almost half (42.5%) of the affected children [22]. WMI is not exclusively associated with prematurity and it is increasingly appreciated in term infants [23][24][25]. Infants with complex congenital heart disease are at particular risk for WMI and delayed brain maturation [26][27][28].…”
mentioning
confidence: 99%
“…Perinatal WMI (including periventricular leukomalacia) was the most common finding, which was seen in almost half (42.5%) of the affected children [22]. WMI is not exclusively associated with prematurity and it is increasingly appreciated in term infants [23][24][25]. Infants with complex congenital heart disease are at particular risk for WMI and delayed brain maturation [26][27][28].…”
mentioning
confidence: 99%
“…PVL is the most frequent pattern of injury in these patients and can be associated with GMH, intraventricular hemorrhage, and periventricular hemorrhagic infarction. 1,2 On the other hand, in full-term neonates, cortical and deep gray matter is mostly affected 3 ; however, recent studies 4,5 have also reported isolated WM lesions in 20% of term neonates with hypoxicischemic insult.…”
mentioning
confidence: 99%
“…However, babies born at early-term gestation can have WMI. Li et al [5] reported 11 babies with WMI out of a cohort of 48 term newborns with encephalopathy. Ten were diffusion positive, 2 had strokes and 1 had basal ganglia injury as well.…”
Section: Term Brain Injurymentioning
confidence: 99%